Urgensi koleksi tandon dan serial sebagai sarana pemenuhan kebutuhan informasi mahasiswa di Perpustakaan UIN Sunan Ampel Surabaya - Suprapto (IJAL (Indonesian Journal of Academic Librarianship), 2021)
This study aims to determine students' perceptions of the importance of Tandon and Serial collections as a means of fulfilling student information needs at the Sunan Ampel UIN Library, Surabaya. The method used is quantitative which displays numbers in the presentation of survey data and questionnaires. There are two analysis results obtained from this study, namely: 1) The procedure for utilizing Tandon and Serial collections begins with tracking the collection through OPAC and filling out the loan form. Borrowing transactions must include a Membership Card with a maximum collection of two copies for two hours. Collections can only be read and photocopied in the library area. 2) Students' perceptions about the importance of using Tandon and Serial collections in fulfilling information needs are in a very good category, because they have a final score of 78 percent.